The Arabidopsis Class III Peroxidase AtPRX71 Negatively Regulates Growth under Physiological Conditions and in Response to Cell Wall Damage. Issue 4 (14th October 2015) - Raggi, Sara; Ferrarini, Alberto; Delledonne, Massimo; Dunand, Christophe; Ranocha, Philippe; De Lorenzo, Giulia; Cervone, Felice; Ferrari, Simone
Abstract : An Arabidopsis peroxidase promotes the production of reactive oxygen species and negatively regulates growth during physiological development and in response to alterations of cell wall integrity. Abstract: The structure of the cell wall has a major impact on plant growth and development, and alteration of cell wall structural components is often detrimental to biomass production. However, the molecular mechanisms responsible for these negative effects are largely unknown. Arabidopsis ( Arabidopsis thaliana ) plants with altered pectin composition because of either the expression of the Aspergillus niger polygalacturonase II (AnPGII; 35S : AnPGII plants) or a mutation in the QUASIMODO2 ( QUA2 ) gene that encodes a putative pectin methyltransferase ( qua2-1 plants), display severe growth defects. Here, we show that expression of Arabidopsis PEROXIDASE71 ( AtPRX71 ), encoding a class III peroxidase, strongly increases in 35S : AnPGII and qua2-1 plants as well as in response to treatments with the cellulose synthase inhibitor isoxaben, which also impairs cell wall integrity. Analysis of atprx71 loss-of-function mutants and plants overexpressing AtPRX71 indicates that this gene negatively influences Arabidopsis growth at different stages of development, likely limiting cell expansion. The atprx71-1 mutation partially suppresses the dwarf phenotype of qua2-1, suggesting that AtPRX71 contributes to the growth defects observed in plants undergoing cell wall damage. Furthermore, AtPRX71 seems to promote the production of reactive oxygen species in qua2-1 plants as well as plants treated with isoxaben. We propose that AtPRX71 contributes to strengthen cell walls, therefore restricting cell expansion, during normal growth and in response to cell wall damage.